1992
DOI: 10.1002/j.1460-2075.1992.tb05582.x
|View full text |Cite
|
Sign up to set email alerts
|

Function in protein folding of TRiC, a cytosolic ring complex containing TCP-1 and structurally related subunits.

Abstract: T‐complex polypeptide 1 (TCP‐1) was analyzed as a potential chaperonin (GroEL/Hsp60) equivalent of the eukaryotic cytosol. We found TCP‐1 to be part of a hetero‐oligomeric 970 kDa complex containing several structurally related subunits of 52–65 kDa. These members of a new protein family are assembled into a TCP‐1 ring complex (TRiC) which resembles the GroEL double ring. The main function of TRiC appears to be in chaperoning monomeric protein folding: TRiC binds unfolded polypeptides, thereby preventing their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
359
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(369 citation statements)
references
References 74 publications
7
359
3
Order By: Relevance
“…Unlike GroEL/ES which can act only post-translationally, TRiC has been shown to fold the discrete domains of firefly luciferase co-translationally (Frydman et al, 1994). From biochemical studies using unfolded firefly luciferase, actin and tubulin, it has been shown that while GroEL/ES failed to fold these model proteins, TRiC was able to mediate their folding, suggesting that it can interact with a different range of substrates via mechanism distinct from class I chaperonins (Frydman et al, 1992;Tian et al, 1995;Yam et al, 2008). A recent study of the TRiC interactome suggests that ~ 10% of newly synthesized cellular proteins, including actin, tubulin, cell cycle regulators and tumor suppressors are TRiC substrates.…”
Section: Ii4113 the Chaperoninsmentioning
confidence: 99%
“…Unlike GroEL/ES which can act only post-translationally, TRiC has been shown to fold the discrete domains of firefly luciferase co-translationally (Frydman et al, 1994). From biochemical studies using unfolded firefly luciferase, actin and tubulin, it has been shown that while GroEL/ES failed to fold these model proteins, TRiC was able to mediate their folding, suggesting that it can interact with a different range of substrates via mechanism distinct from class I chaperonins (Frydman et al, 1992;Tian et al, 1995;Yam et al, 2008). A recent study of the TRiC interactome suggests that ~ 10% of newly synthesized cellular proteins, including actin, tubulin, cell cycle regulators and tumor suppressors are TRiC substrates.…”
Section: Ii4113 the Chaperoninsmentioning
confidence: 99%
“…This chaperonin, designated by Chaperonin Containing TCP1 (CCT) [10], is a hetero-oligomeric complex that in mammalian cytosol has a molecular mass of about 850-900 kDa. It is composed of seven to nine distinct polypeptides in the 52-65 kDa size range [10][11][12]. In mouse, genes coding for eight of the CCT subunit polypeptides have already been isolated and were designated as CCT0t (for the original TCP1), CCT [3 .... and CCT~ [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in vitro CCT is involved in the folding of actin [17,18], tubulin [12,19] and firefly luciferase [12,20]. In vivo studies indicate that newly synthesized a-and 13-tubulin and actin enter in a 900 kDa complex containing TCP1 and that tubulin is released from this complex competent to form heterodimers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Both GroEL and CCT have a double-ring cylindrical structure and bind their protein substrates within the central cavity (Braig et al, 1993;Marco et al, 1994). Both require ATP binding and hydrolysis for their folding activity (Gao et al, 1992;Gething & Sambrook, 1992;Frydman et al, 1992;Yaffe et al, 1992). While GroEL is composed of identical subunits (7 per ring), CCT contains 8-9 nonidentical but related subunits per ring (Frydman et al, 1992;Gao et al, 1992;Lewis et al, 1992;Kim et al, 1994;Kubota et al, 1994Kubota et al, , 1995a.…”
mentioning
confidence: 99%
“…Both require ATP binding and hydrolysis for their folding activity (Gao et al, 1992;Gething & Sambrook, 1992;Frydman et al, 1992;Yaffe et al, 1992). While GroEL is composed of identical subunits (7 per ring), CCT contains 8-9 nonidentical but related subunits per ring (Frydman et al, 1992;Gao et al, 1992;Lewis et al, 1992;Kim et al, 1994;Kubota et al, 1994Kubota et al, , 1995a. Another striking difference between the two chaperonins is their different substrate specificity.…”
mentioning
confidence: 99%